The relationship between motives of earning management and asymmetric cost behavior: Comparative study between public and private sector companies - Mohamed , Moamen; Soliman, Mohamed (The Arab Journal of Administration, 2023)
This research aims to investigate the relationship between the management’s motivations towards earnings management and asymmetric cost behavior, by addressing the impact of government ownership on the nature of this relation. In order to test the hypotheses of the study, a sample of listed non-financial companies in the Egyptian market was used for the period from 2009 to 2017 with 792 observations. The results reached the level of the sample as a whole to: the existence of a significant and positive relationship between management’s motives towards “avoiding political pressures, complying with debt covenants requirements” and asymmetric cost behavior. It also reached to the existence a significant and negative relationship between management’s motives towards “reducing income figure dispersion, avoiding income decline, avoiding loss” and asymmetric cost behavior. The results of the comparison between the two samples of government-owned and privately owned companies indicate to the presence of significant and statistically significant differences, as the study found that there is no relationship between management’s motives towards “avoiding loss, avoiding income decline, dispersing income figure” and the asymmetric cost behavior of companies with government ownership; While the results indicate to the existence of a significant and negative relationship between management’s motives towards “avoiding loss, avoiding income decline, dispersing the income figure” and asymmetric cost behavior companies with private ownership .